[PP.06.25] BETA-BLOCKERS ARE THE ONLY ANTIHYPERTENSIVE DRUGS THAT BLUNT THE DURATION OF WHITE-COAT EFFECT ESTIMATED WITH AMBULATORY BLOOD PRESSURE MONITORING. (September 2017) - Salvo, F.; Albano, M.; Vallo, C.; Lonati, C.; Fogliacco, P.; Errani, A.R.; Berardi, M.; Meinero, V.; Muzzulini, C.L.; Morganti, A.
Abstract : Objective: The presence of white-coat effect (WCE) on ambulatory blood pressure monitoring (ABPM) can increase mean blood pressure (BP) values determining an overestimation of the diagnosis of arterial hypertension. We previously found that WCE duration (WCEd) is longer in females than in males and significantly blunted by beta-blockers in males; however the influence of the other antihypertensive drugs was not established. Design and method: We analysed 281 ABPM (M/F 101/180) in which the first systolic value was at least 10 mmHg higher than mean diurnal systolic BP (mDSBP). WCE was evaluated during the first two hours of recording as the mean value of systolic BP (WCE magnitude, WCEm) and as WCEd i.e. the sum of the time intervals in minutes (min) following a systolic BP value of at least 10 mmHg higher than mDSBP. The relation between WCE and drug classes (angiotensin-converting enzyme/angiotensin receptor blockers, beta-blockers, calcium channel blockers, thiazide diuretics, alpha-blockers, central alpha-agonists and anti-aldosterone) was evaluated with a multivariate regression analysis with a p-value < 0.01 considered as statistically significant. Results: Mean age was 65 ± 1 years (M/F 66 ± 1/64 ± 1 years, n.s.) and overall mDSBP was 138 ± 1 mmHg, without differences between genders. Mean WCEm and WCEd were respectively 151 ± 1 mmHg (M/F 149 ± 2/152 ± 1, n.s.) and 63 ± 1.5 min (M/F 59 ± 2/66 ± 2, p < 0.02). The multivariate regression analysis showed that WCEd was correlated only with beta-blockers and male gender (table), whereas there were no relationship of WCEm with any drugs. Figure. No caption available. Conclusions: WCEd is shorter in men than in women regardless of drug therapy and beta-blockers are the only antihypertensive drugs that seem to reduce WCEd estimated with ABPM, whereas they do not affect WCEm.